(untitled) (Carte Romanze, 2024)
The texts of the so-called medieval Waldensian literature are preserved in a corpus of manuscripts, of which we do not know the contexts of creation; however, some of them were certainly kept - since the early 17th century, but perhaps even in the decades prior - in the traditional areas of settlement of Alpine Waldensian communities (the present-day Waldensian Valleys). This contribution aims to illustrate the centers of culture and education active in the Waldensian Valleys and the surrounding area, where it was possible to acquire literacy in the Latin language and higher education, skills undoubtedly possessed by some of the authors of Waldensian literature. It is conceivable that in these environments, a portion of the Waldensian preachers was also formed, among whom several had previously been members of the Catholic clergy.